2017
DOI: 10.5312/wjo.v8.i9.710
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage anterior debridement and reconstruction with tantalum mesh cage for complicated infectious spondylitis

Abstract: AIMTo evaluate the clinical and radiographic results of patients with complicated infectious spondylitis treated with single-stage anterior debridement and reconstruction using tantalum mesh cage (TaMC) followed by immediate instrumentation.METHODSSingle-stage radical debridement and subsequent reconstruction with TaMC instead of autograft or allograft were performed to treat 20 patients with spinal deformity or instability due to complicated infectious spondylitis. Clinical outcomes were assessed by careful p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Patients with infectious spondylitis are treated with radical debridement followed by anterior column reconstruction us- ing various biological and mechanical spacers, including autografts, allografts, and metal cages 23) . The defect created after debridement is commonly repaired using autogenous bone grafts from the fibula or the iliac crest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with infectious spondylitis are treated with radical debridement followed by anterior column reconstruction us- ing various biological and mechanical spacers, including autografts, allografts, and metal cages 23) . The defect created after debridement is commonly repaired using autogenous bone grafts from the fibula or the iliac crest.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological and mechanical spacers such as allografts, autografts, and metal cages are used for post-corpectomy anterior column reconstruction. To date, reconstruction using a metal cage with allogenic bone grafts after radical debridement of the lesion is controversial 23) .…”
Section: Introductionmentioning
confidence: 99%
“…Porous Ta implants were shown to be effective in the second-stage revision of prosthesis infection and the treatment of infectious spondylitis . Upon performing a retrospective analysis of 20 patients who underwent structural reconstruction with a tantalum mesh cage (TaMC) due to infectious spondylitis, it was found that the application of TaMC could significantly improve the function of the patients, with only one patient developing refractory infections that required further debridement (Figure A) . In another study, the data from 60 patients who underwent second-stage revision with porous Ta cones due to knee prosthesis infection indicated that the implantation of porous Ta cones significantly improved the functional scores (Figure B) .…”
Section: Clinical Applications Of Ta In Ibds Treatmentmentioning
confidence: 99%
“…80 Upon performing a retrospective analysis of 20 patients who underwent structural reconstruction with a tantalum mesh cage (TaMC) due to infectious spondylitis, it was found that the application of TaMC could significantly improve the function of the patients, with only one patient developing refractory infections that required further debridement (Figure 7A). 80 In another study, the data from 60 patients who underwent second-stage revision with porous Ta cones due to knee prosthesis infection indicated that the implantation of porous Ta cones significantly improved the functional scores (Figure 7B). 79 There were only two (3.3%) unsuccessful cases resulting from the recurrence of infection, and neither were related to porous Ta cone mechanics.…”
Section: Clinical Applications Of Ta In Ibds Treatmentmentioning
confidence: 99%
See 1 more Smart Citation